Does paddy cultivation in Malaysia contribute to increased CO2 emissions?: an econometric analysis - Alias, Emmy Farha; Abdul Hamid, Baharom; Radam, Alias; Yacob, Mohd Rusli (School of Social Sciences, Universiti Sains Malaysia, 2012)
This study was conducted to investigate whether paddy cultivation in Malaysia do indeed contribute to increased CO2e. Johansen (1991) co-integration method was used to investigate the relationship between these variables, and the result clearly shows that they are highly co-integrated or literally means that they (both variables) share long term time trending patterns. The long run relationship is further investigated based on granger causality and vector error correction model (VECM), and the result again clearly shows that paddy production indeed granger causes the increased CO2e. Dynamic Ordinary Least Square (DOLS) method was also employed to check the robustness and consistency of the findings and the results are consistent and robust with the VECM estimations. The findings of the study clearly show the dire needs for the government to invest more on the R&D in the paddy production sector in order not to further deteriorate the environment albeit CO2e while securing the food security.